Author Correction: Association of serotonin system-related genes with homicidal behavior and criminal aggression in a prison population of Pakistani Origin - Muhammad Imran Qadeer (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.